Influence of low noise barrier height on sound insertion loss - Tumavičė, Aja; Jasiūnienė, Vilma (International Conference “Environmental Engineering”, 2023)
Ensuring the best possible quality of the living environment is the worldwide aim. One of the very important factors strongly affecting people’s health is the traffic produced noise, the reduction of which to permissible values can significantly improve the well-being of those living and working near traffic areas. On railway lines where rolling stock does not exceed 250 km/h, low noise barriers may be used. The aim of the study is to determine which low noise barriers are the most effective in Lithuanian conditions. This article analyses the insertion loss of low noise barriers of different heights installed at different distances. The obtained results show that the highest loss insertion in all 45 m long low sound barriers at a distance of 45 m from the track axis was found for the 1.2 m high straight sound barrier located 2.6 m from the track axis and the 1.3 m high and inverted L-shaped (bracket length – 0.65 m) noise barriers located at a distance of 3.1 m from the track axis. Their insertion loss is 2.9–4.6 dBa, depending on the running speed (slightly) and the level of the microphone.